Comparative analysis of postoperative outcomes following surgical and transcatheter edge-to-edge mitral valve repair for secondary mitral regurgitation: a meta-analysis & systematic review - Hanafy, Dudy A.; Sudirman, Adrian R.; Rahmawati, Sari; Satria, Hendry R.; Safitri,; Nursalim, Stefanus; Bachmid, Muhammad R.; Fardhani, Dwi G.; Soetisna, Tri W.; Sugisman, (Frontiers in Surgery, 2025)
IntroductionMitral regurgitation (MR) affects approximately millions of people globally, predominantly older adults, leading to 0.88 million DALY and 34,000 deaths in 2019. Both ESC and ACC/AHA guidelines recommend intervention either surgery or transcatheter for secondary MR despite optimal medical therapy. The comparative effectiveness of SMVr vs. TEER for managing secondary MR remains uncertain, prompting a systematic review to assess outcomes, safety, and long-term implications.MethodThis systematic review and meta-analysis were carried out and documented according to the PRISMA 2020 guidelines. Searches were conducted in the Embase, EBSCOHost, Medline, Sage, Science Direct, and Scopus databases.ResultThis meta-analysis included eight studies and 6224 patients. Both SMVr and TEER showed similar rate of in-hospital mortality (3.85% vs. 2.83%, RR = 2.54; 95% CI = 0.59–10.95; p = 0.21; I2 = 57%), while SMVr was associated with a significantly lower incidence of post-discharge residual MR compared to TEER (RR = 0.27; 95% CI = 0.16–0.45; p < 0.01; I2 = 0%). However, SMVr showed a higher incidence of neurologic events, including stroke or TIA (1.89% vs. 0.94%, RR = 1.88; 95% CI = 1.16–3.05; p = 0.001; I2 = 0%). The rates of acute renal failure (5.26% vs. 5.29%, RR = 1.23; 95% CI = 0.84–1.80; p = 0.28; I2 = 9%) and postoperative myocardial infarction (1.91% vs. 1.81%, RR = 1.07; 95% CI = 0.71–1.62; p = 0.73; I2 = 0%) were higher in the SMVr group, but this was statistically insignificant. Mid-term mortality analysis favored SMVr over TEER, with lower mortality rates observed in SMVr patients (Rate Ratio 0.74; 95% CI, 0.63–0.88; p < 0.001; I²=27%), lower reintervention rates (RR = 0.29, p < 0.001), lower incidence rate ratio of recurrent MR (Rate Ratio = 0.56; 95% CI = 0.40–0.78; p = 0.0005; I2 = 0%) and heart failure rehospitalization (Rate Ratio = 0.81; 95% CI = 0.68–0.97; p = 0.02; I2 = 5%). SMVr patients were more likely to experience improvement in functional status (NYHA) compared to TEER patients (RR = 1.14, p < 0.006).ConclusionSMVr has demonstrated better mid-term outcomes than TEER, including lower mortality rates, fewer reinterventions and rehospitalization, and improved functional status in patients with mitral regurgitation.Systematic Review Registrationidentifier [CRD42024538771].